PERAN CAMAT DALAM PELAKSANAAN PEMERINTAHAN UMUM BERDASARKAN UNDANGÂUNDANG NOMOR 23 TAHUN 2014 (STUDI DI KECAMATAN JATINANGOR KABUPATEN SUMEDANG) - Hutagaol, Yesiska Pebrina (Fakultas Politik Pemerintahan, 2017)
ABSTRACT The concept of government affairs generally evolved over time. Before the New Orde Government affairs generally simply point to the local government affairs in general and there is no clear boundary between central and local government affairs and handed over to representatives of the central government in the regions. New Orde government affairs generally is the whole affair the rest of the authority of the central government, whose implementation in decontration to the head region (up to the district level). Reform, the implementation of broad autonomy does not provide clear limits on the implementation of government affairs public, but in Act No. 23 of 2014 the nomenclature of government affairs public reappears in Article 225 paragraph (1) section (1) which states that the Head menyeleggarakan Government Affairs general delegated Regents/Mayors at district level. This research uses descriptive qualitative method with inductive approach. The data in this research analysis by Miles and Huberman method, stageconsisted of data reduction, data presentation, and verification conclusion. Based on the research field, the results are as follows: 1. Implementation of government affairs generally come from the president the authority delegated to regents and mayors will be forwarded to head with financing through the state budget process. 2. FORKOMPIMCA chaired by head of district. 3.Model implementation of government affairs generally run of head of district jatinangor is the third model is the residue government affairs in this public government affairs are handled by the respective levels of government. Keywords: